Serum protein concentrations, including acute phase proteins, in calves experimentally infected with Salmonella Dublin - Silva, Daniela Gomes da [UNESP]; Silva, Péricles Ricardo Lacerda e [UNESP]; Silva, Paulo César da [UNESP]; Fagliari, José Jurandir [UNESP] (Colégio Brasileiro de Patologia Animal - CBPA, 2011)
O objetivo do estudo foi avaliar as concentrações séricas de proteínas em bezerros inoculados experimentalmente com Salmonella Dublin. Foram examinados 12 bezerros sadios da raça Holandesa com 10 a 15 dias de idade, distribuídos aleatoriamente em dois grupos, controle e infectado experimentalmente com 10(8) UFC de Salmonella Dublin. As amostras de sangue foram colhidas minutos antes e 12, 24, 48, 72, 96, 120 e 168 horas após a inoculação. As concentrações séricas das proteínas ceruloplasmina (125.000 Da), haptoglobina (45.000 Da), glicoproteína ácida (40.000 Da) e proteína de peso molecular de 34.000 da foram significativamente maiores nos bezerros infectados do que nos do grupo controle. Portanto, o estudo mostrou que a infecção por S. Dublin pode elevar a concentração de certas proteínas séricas em bezerros.

The aim of this study was to evaluate serum protein concentrations in calves experimentally inoculated with Salmonella Dublin. Twelve healthy 10 to 15-day-old Holstein calves were randomly allotted into two groups, control and infected with 10(8) CFU of Salmonella Dublin orally. The calves were subjected to physical evaluation and blood samples were collected shortly before administration of the bacteria and also 24, 48, 72, 96, 120 and 168 hours post-infection. The concentration of serum proteins was determined through sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE). Thirty serum proteins ranging from molecular weight of 24,000 da to molecular weight of 236,000 da were detected. Serum concentrations of ceruloplasmin (125,000 Da), haptoglobin (45,000 Da), acid glycoprotein (40,000 Da) and a 34,000 da protein were significantly increased in the experimentally infected calves, when compared with their concentrations in the control animals. Therefore, this study showed that S. Dublin infection could lead to the increase of certain serum proteins in calves.
Teores séricos de proteínas, incluindo proteínas de fase aguda, em bezerros infectados experimentalmente com Salmonella Dublin
Keywords: Salmonella Dublin; SDS-PAGE; serum proteins; Calves; Salmonella Dublin; SDS-PAGE; proteínas séricas; Bezerros